Comparative evaluation of the pushout bond strength of two root-end materials: An in vitro study - Hegde, Nidhi (J Conserv Dent, 2019)
AIM: The aim of this study is to evaluate the pushout bond strength of two bioceramic materials, two component calcium trisilicate material (biodentine), and premixed calcium trisilicate putty (Endosequence root repair material-fast set putty). SUBJECTS AND METHODS: 20 maxillary incisors were used in the study. Apical sections of 3mm were obtained and retro cavities to a depth of 3mm were prepared using a straight fissure bur. Another transverse section was made 4-mm coronal to the previous section. The specimens were placed into acrylic resin rings and separated into two groups and their cavities filled with the materials. The pushout test was carried out using a universal testing machine at a cross head speed of 0.5 mm/min, and the specimens were examined in a stereomicroscope at to evaluate the modes of failure. STATISTICAL ANALYSIS: The pushout bond strength values were analyzed using the unpaired t-test, and the modes of failure were compared using Fisher's exact test. RESULTS: The pushout bond strength was seen to be significantly higher (P < 0.001) for the two-component calcium trisilicate material (11.596 ± 3.309). Cohesive failure patterns were observed in both the test groups. CONCLUSION: Two component calcium trisilicate material demonstrated higher bond strength values to apical dentine.